2020
DOI: 10.5276/jswtm/2020.15
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical Analysis of Portland Cement Pastes Rehydrated

Abstract: Hydrated products, such as (hydrated) cement pastes, decomposition through physical-chemical alterations when submitted to high temperatures. One of the main factors that lead to microstructural changes during calcination up to 800ºC, is the dehydration phases of hydrated Portland cement. The present study sought to characterize crystalline phases occurring before and after calcination to the produced pastes using X-ray diffraction (XRD) analysis. Cement pastes were produced using Portland cement CP V-ARI RS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…At this point, free water emanating from C-S-H was also observable [62]. Another significant peak around 750 • C can be attributed to the decomposition or decarbonization of CaCO 3 (Calcite) [63]. Notably, the DTA and TGA profiles indicated a relatively higher C-S-H decomposition in T20 compared to T0 (the reference mortar) at 100 • C, present in both mixes.…”
Section: Ftirmentioning
confidence: 92%
“…At this point, free water emanating from C-S-H was also observable [62]. Another significant peak around 750 • C can be attributed to the decomposition or decarbonization of CaCO 3 (Calcite) [63]. Notably, the DTA and TGA profiles indicated a relatively higher C-S-H decomposition in T20 compared to T0 (the reference mortar) at 100 • C, present in both mixes.…”
Section: Ftirmentioning
confidence: 92%
“…Vicat apparatus was used to determine the pastes' water consistency by ASTM: C191 [21]. The compressive strength of three cubic pastes representing the same binder pastes and curing time was measured according to ASTM C-150 [18,22], and the average result was recorded.…”
Section: Methods Of Investigationmentioning
confidence: 99%
“…The total weight losses observed at this stage are 1.80 and 2.55% for, respectively, composition 1 and composition 4. Santos et al [52] reported that the complete decomposition of ettringite takes place around the temperature range of (90-100) • C, while C-S-H in gel form decomposes within the temperature range of (200-450) • C. However, scientists [53][54][55] reported a wider range of decomposition temperatures for analyzed compounds. permitted temperature increase.…”
Section: Analysis Of the Thermal Stabilitymentioning
confidence: 99%